Peningkatan Produksi Susu Sapi Perah di Peternakan Rakyat Melalui Pemberian Katuk-IPB3 sebagai Aditif Pakan - Agik Suprayogi; Hadri Latif; . Yudi; Asep Yayan Ruhyana (Jurnal Ilmu Pertanian Indonesia, 2013)
This study was to evaluate the depolarization of katuk leaves (Katuk-IPB3) as a feed additive for increasing dairy cattle milk yield at the farmer condition. Sixteen selected lactating cattles were divided into 4 groups; 4 cattles in each group. One group as a control, and 3 treated groups, namely P100, P150, and P200. P100, P200, and P300 were designated as cattle group given powder of Katuk-IPB3 as much as 100 g/day, 150 g/day, and 200 g/day, respectively. The treatment was executed in the 10 days before pregnancy up to 2 months lactating periods. Katuk-IPB3 showed significant positive response on the produced milk on all dose levels as compared to the control group, i.e. 35, 40, and 34% increased, respectively. The possible reason is that the nonpolar active compounds in the Katuk-IPB3 play an important role to the hormonal and metabolic action in the lactating mammary gland.